The Endometriosis Impact Questionnaire (EIQ): a tool to measure the long-term impact of endometriosis on different aspects of women's lives - Maryam Moradi; Melissa Parker; Anne Sneddon; Violeta Lopez; David Ellwood (BMC, 2019)
Abstract Background Endometriosis is a chronic disease impacting on many aspects of a woman's life. Because of the chronic and recurring nature, many of the impacts of endometriosis could be missed using existing questionnaires which focus on recent events. Therefore, a questionnaire with a long-term perspective is necessary. This study aimed to develop and evaluate a questionnaire to measure the long-term impact of endometriosis on different aspects of women's lives. Methods Through a methodological design, phase 1 was qualitative and phase 2 was a cross-sectional study. The original 100 EIQ items were developed based on results from an earlier qualitative study and literature review. Through a process of assessing face and content validity this was reduced to 66 items. The psychometric properties of the final 63 item EIQ were evaluated through a web-based survey with data from 423 responders with a self-reported surgically-diagnosed endometriosis. Results Participants were aged 16-58 years. Exploratory factor analysis of a 66-item EIQ was established with 423 responders. The final 63-item EIQ contained six dimensions including: 33-item physical-psychosocial; 3-item fertility; 7-item sexual; 11-item employment; 6-item educational; and 3-item lifestyle. Cronbach's alpha of 0.99 for the whole 63-item EIQ, and 0.84 to 0.98 for the dimensions suggests a very good reliability. High positive correlations between the EIQ and the EHP-5 (altered recall period) indicated good evidence of concurrent validity. High intra-class correlations indicated very good test-retest reliability. Conclusions The EIQ, as a disease-specific questionnaire, could be used to provide a better understanding of the impact of endometriosis on different aspects of life, to better meet the needs of women. We recommend additional studies to establish validity evidence for the EIQ, including studies in other countries and languages.